Sostenibilidad ambiental de polímeros para empaques flexibles y su comparación con las nuevas tecnologías (2014)
What article pretends to emphasize, taking an LCA proposed model, it brings the discussion to some completely defined indicators, which are conceptually involved in Sustainability. This means, it is just under different kind of indicators: social, environmental, economics, that an option can be declared more sustainable than other. However, paper outlines environmental issues and just shows the others that are also important.